Rectangular Stress-block Parameters for Fly-ash and Slag Based Geopolymer Concrete - Tran, T.; Pham, Thong; Hao, Hong (2019)
Although there has been a numerous quantity of studies investigating the mechanical properties of geopolymer concrete (GPC), parameters for designing GPC structures are still not systematically investigated and carefully justified. ACI rectangular stress-block parameters are able to predict well the strength of conventional concrete structures but their applicability for GPC is questionable. This study aims to establish new sets of rectangular stress-block parameters for GPC with a broad range of the compressive strength up to 66 MPa. The proposed rectangular stress-block parameters in this study are based on two analytical concrete stress-strain models and measured curves from previous studies of GPC materials. The results from this study show that the use of ACI recommendations for concrete structure in designing GPC beams is still acceptable with high accuracy. However, the axial load-carrying capacity of GPC columns computed by ACI parameters deviate significantly from the experimental results while the proposed parameters provide a good correlation with these experimental data. The significant difference is mainly due to the modification of k3, which is the ratio of concrete strength in real structures to standard cylinder samples. This study suggests that the assumption of k3 = 0.9 in previous studies for conventional Portland concrete is not suitable for use in deriving the stress-block parameters of GPC. In some cases, this ratio should be reduced to 0.7 depending on the curing condition.